2009
DOI: 10.1002/pits.20426
|View full text |Cite
|
Sign up to set email alerts
|

Use and impact of antidepressants in the school setting

Abstract: Depression-based presentations constitute some of the most commonly seen psychiatric manifestations within the school-age population. In conjunction with increased numbers of children and adolescents being diagnosed with depressive symptomology over the past 2 -3 decades, there has been seen a concurrent increase in the amount of antidepressant agents being prescribed within this group. This increase is largely related to the development of the newer class antidepressants, the selective serotonin reuptake inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Progress monitoring could also be used to inform risk-benefit analysis and decision-making about psychosocial treatment alternatives. School psychologists can also consult with teachers and parents to suggest accommodations and modifications that may mitigate the impact of these SEs on school performance and behavior (Kubiszyn, 2011; Noggle & Dean, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Progress monitoring could also be used to inform risk-benefit analysis and decision-making about psychosocial treatment alternatives. School psychologists can also consult with teachers and parents to suggest accommodations and modifications that may mitigate the impact of these SEs on school performance and behavior (Kubiszyn, 2011; Noggle & Dean, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of effective antidepressants beginning in the 1950s also produced an increase in the daily functioning of individuals and helped to reduce the rate of suicide among patients. Although many patients did benefit from the first generation of early medications, the side-effect profiles often were viewed as particularly detrimental and in some cases could increase the availability of means of suicide (see Noggle & Dean, 2009). An increased availability of means is particularly problematic for patients who may act impulsively when contemplating suicide.…”
Section: Trends In Medication Use and Side Effectsmentioning
confidence: 98%
“…As a result, research has demonstrated the utility of a number of these agents for the partial remediation of the signs and symptoms of many childhood disorders. In the preceding articles, advances in the pharmacological treatment of ADHD (see Vaughan, Roberts, & Needelman, 2009); bipolar disorder, schizophrenia, and other psychotic disorders (see Noggle & Dean, 2009a); depressive disorders (see Noggle & Dean, 2009b); sleep disturbances (see Hamilton, 2009); seizures and epilepsy (see Titus & Thio, 2009); and pervasive developmental disorders (see Floyd & McIntosh, 2009;Noggle & Dean, 2009a) have been discussed. In addition, issues pertaining to the changing role of psychological professionals within the schools have been offered.…”
Section: Southern Illinois University School Of Medicinementioning
confidence: 99%